Using semi-supervised learning models for creating a new fake news dataset from Twitter posts: a case study on Covid-19 in the UK and Brazil - Nascimento, Tuany Mariah Lima do (2022)
Coordenação de Aperfeiçoamento de Pessoal de Nível Superior - CAPES